Clinical and economic profile of prucalopride in the treatment of chronic constipation in women - Stanghellini, Vincenzo; Eandi, Mario (Farmeconomia. Health economics and therapeutic pathways, 2012)
Chronic constipation is a common disorder, especially in women. Options available for different subgroups of constipation are limited and in most cases unsatisfactory. The most severe forms of chronic constipation often require the use of laxatives in high doses or the use of invasive therapies. The introduction of a new drug, such as prucalopride, active in promoting intestinal transit, can help to improve the therapy of patients with chronic idiopathic constipation who have not found relief from previous treatment with laxatives. In this review, after a brief discussion of pathophysiology and pharmacotherapy of chronic constipation, we evaluate the pharmacological profile, therapeutic and cost of prucalopride, recently authorized in the EU countries and also available in Italy for the treatment of chronic constipation in women who did not benefit from the use of laxatives